Perfil de ácidos orgânicos e ácidos graxos durante a secagem de café arábica - Calderón, Renso Alfredo Aragón (2018)
The interaction of the variety, soil, altitude, exposure, handling, processing, drying, storage, roasting and preparation factors are responsible for the complexity characteristics obtained in the specialty coffee beverage. Different studies have evaluated the chemical differences of coffees with and without the presence of part of the pericarp during processing. However, most were mostly made in the raw or uncontrolled grain of all other factors during the process. It is believed that it is possible to establish a point during drying in which it is possible to detect where the differences on chemical composition between natural and peeled coffee occur and which chemical compounds predominate. In this study, samples of Coffea arabica L., Catuaí Amarelo variety, from a single batch, were collected with procedures suitable for the production of specialty coffees and simultaneously submitted to drying in a fixed layer dryer under forced convection. Samples with the presence of the intact fruit (natural coffee) and samples with exocarp and mesocarp removal (demucilated coffee) were established. During drying, samples with water contents 53±2%, 36±2%, 19±2% and 11±1% (w.b.) were taken for analysis of the organic acids profile by HPLC liquid chromatography, fatty acid profile by GC-MS gas chromatography and analysis of volatile compounds in the roasted coffee bean by GC-MS. For organic acids and fatty acids, a completely randomized factorial design was done for four water contents (% w.b.), two types of processing (dry and wet), with three replicates. The organic acid and fatty acid profile was analyzed by Scott-Knott's mean comparison test (p <0.05) and PCA. The volatile compounds were analyzed with PLS-DA. Sensory analysis was performed using the SCA methodology. For both processing methods, the organic acid profile showed a decrease in the content of citric, succinic and acetic acid, during the drying phase between 36±2% and 19±2% (w.b.). The content of quinic acid depends on the interaction between the processing method and the water content, which decreases in phase between 36±2% and 19±2% (w.b.) for the natural coffee. However, for the demucilated coffee, it remains unchanged during drying. The fatty acids vary depending on the water content for each processing, but at the end of drying the natural and demucilated coffee have similar values. Predominant volatile compounds were identified in natural coffee: acetic acid, ethyl ester, 2-methyl butanal, 3-methyl butanal, 2,5-dimethyl pyrazine, 2,3-dimethyl pyrazine, and the sensory profile of the natural coffee beverage was different of the demucilated.